Determination of water soluble and insoluble (dilute-HCl-extractable) fractions of Cd, Pb and Cu in Antarctic aerosol by square wave anodic stripping voltammetry: distribution and summer seasonal evolution at Terra Nova Bay (Victoria Land). - ANNIBALDI, ANNA; TRUZZI, Cristina; ILLUMINATI, Silvia; SCARPONI, Giuseppe; E. BASSOTTI (2007)
Eight PM10 aerosol samples were collected in the vicinity of the “Mario Zucchelli” Italian Antarctic Station (formerly Terra Nova Bay Station) during the 2000–2001 austral summer using a high-volume sampler and precleaned cellulose filters. The aerosol mass was determined by differential weighing of filters carried out in a clean chemistry laboratory under controlled temperature and humidity. A two-step sequential extraction procedure was used to separate the water-soluble and the insoluble (dilute-HCl-extractable) fractions. Cd, Pb and Cu were determined in the two fractions using an ultrasensitive square wave anodic stripping voltammetric (SWASV) procedure set up for and applied to aerosol samples for the first time. Total extractable metals showed maxima at midsummer for Cd and Pb and a less clear trend for Cu. In particular, particulate metal concentrations ranged as follows: Cd 0.84–9.2 μg g−1 (average 4.7 μg g−1), Pb 13.2–81 μg g−1 (average 33 μg g−1), Cu 126–628 μg g−1 (average 378 μg g−1). In terms of atmospheric concentration, the values were: Cd 0.55–6.3 pg m−3 (average 3.4 pg m−3), Pb 8.7–48 pg m−3 (average 24 pg m−3), Cu 75–365 pg m−3 (average 266 pg m−3). At the beginning of the season the three metals appear widely distributed in the insoluble (HCl-extractable) fraction (higher proportions for Cd and Pb, 90–100%, and lower for Cu, 70–90%) with maxima in the second half of December. The soluble fraction then increases, and at the end of the season Cd and Pb are approximately equidistributed between the two fractions, while for Cu the soluble fraction reaches its maximum level of 36%. Practically negligible contributions are estimated for crustal and sea-spray sources. Low but significant volcanic contributions are estimated for Cd and Pb (∼10% and ∼5%, respectively), while there is an evident although not quantified marine biogenic source, at least for Cd. The estimated natural contributions (possibly including the marine biogenic source) cannot account for the high fractions of the metal contents, ...